APLIKASI WEB MOBILE TOKO ONLINE MOBIL BEKAS PADA ANUGRAH MOBIL (Information Technology and Telematics, 2014)
Abstract The rapidly development a technology now, it is possible for human to get easy of using technology, One of utilization of web technology, people who need information or developed business. One of them is buying and sales second car. The use of web mobile is easy to learn, Cheep for production, standardization and easy for distribution. Web mobile is the only one platform which available and can work well for all software mobile.  The activity and information of show room at this time promoted by offline, and now will chance to online shop concept. So, costumer can access information about car that ready in Anugrah shop and it is possible to get information that their need. The purpose of this research is make a application web mobile for online shop second car to Anugrah mobil where the customer can access information  more detail about the specification  of the car. The benefit of this research is giving an easy to get information buying and sell second hand car and easy accessed by web mobile. The result of this research is to give information buying and sell second car by using mobile software. This application made by using PHP program and use BOOTSTRAP as layout display. Key word: web mobile, online shop, second car.